Taxpayer Compliance in Service Tax: An Indirect Compliance Study - Sor Tin, Saw (2016)
This study investigates the influence of tax audit variables on taxpayer compliance (TC) and the mediating effect of tax return filing (TRF) on taxable sales and TC. The study sample comprised 250 service tax (ST) licensees registered in Federal Territory of Kuala Lumpur. The ratio of taxpayer compliance in terms of ‘declared service tax’ to ‘actual service tax’ for the period year 2010 to 2012 is the basis for determining a compliance rate for the dependent variable in the analysis. Direct or interfaced data obtained from questionnaire, tax audit cases closed in year 2012 with supporting database are used for statistical analysis, validity or reliability measure. Six hypotheses are tested for their correlation relationship with TC factor. Multiple linear regression (MLR) analysis is performed to determine the set of significant continuous variables for ST noncompliance (n=150) and to test the adapted simplified Fischer et al. (1992) TC model. Descriptive statistics using frequency, percentage and mean analysis are used to evaluate compliance level for 250 audited taxpayers. ANOVA with post-hoc Tukey HSD and Kruskal-Wallis test are performed on five categorical variables to test for statistical significance difference between independent groups. The results obtained show that there is a significant negative correlation between the ‘tax deficiency claim , proportional penalty’ and TC; and a positive correlation between the ‘taxable sales level, tax return filing’ and TC. The new TC (MLR) model comprises variables: three noncompliance opportunity (NCO), two tax system/structure (TSS) and taxpayer compliance. There is a marginally significant mediating effect of TRF on the relationship between taxable sales and TC. The study contributes to the body of knowledge by uncovering the significant MLR model and the various significant tax audit variables of TC. The evidences reported on a new tax compliance model will help shed light on the influence of NCO and/or TSS variables on taxpayer compliance in the taxable services sector in Malaysia. The results also offer suggestions on public enforcement strategy of coercion versus cooperation approach for policy makers and tax authorities to enforce compliance, elicit voluntary compliance, plan and implement an effective tax policy and tax administration.